A time-resolved synchrotron energy dispersive diffraction study of the dynamic aspects of the synthesis of ettringite during minepacking - Muhamad, M. N. (Elsevier Science, 1993)
Synchrotron radiation - energy dispersive diffraction has been used as a method for in-situ studies on the hydration of cements. The rapid data capture of the technique permits a time-resolved analysis of hydrating cement species under realistic (chosen) conditions. We report on a study of the early hydration of minepack mixtures forming ettringite: the growth can be perceived over steps as small as 20 seconds, as also the shifts in diffraction peak positions which are interpreted in terms of a time-dependent composition of the ettringite phase